Use of modern information technologies and students command work in teaching educational course “information technologies Management in Higher educational establishments” (Journal of Information Technologies in Education (ITE), 2007)
Authors present the article, exposing possibilities of the use of new information technologies and command work of students for subjects which are taught in universities, on the example of course „Information technologies management in higher educational establishments”. The purpose of application of work in microgroups is providing practice and development of effective command abilities and critical thinking for students, and also improvement of practical skills in information technologies and computer technique, theoretical and applied knowledges in management by a discussion and teaching.